(untitled) (Journal of Libya for geographical studies, 2022)
Drawing a geomorphologic map of the study area in Al-Jabal Al-Akhdar, providing a classification of relief based on morphological criteria and containing clear morphological content with some morphological elements. Geomorphologic mapping is one of the main research methods in geomorphology, as it is not only of scientific importance, but also of practical importance. The area lies between 21 and 59 and 22 and 12 east and between 32 and 45 and 32 and 58 north latitude. The basis of the work was a topographic map with a contour interval of 20 m and a scale of 1 to 50,000. Geomorphologic features were recognized from the map such as coastal plain, cliffs, steps, etc. to produce a preliminary map of major features. This was followed by a careful analysis of the stereo pairs of the aerial photographs (the pairs of the aerial photographs were examined using stereoscopic, and the scales of the photographs were 1:20000, in order to obtain detailed observations that were not shown by the topographic or geological maps. A variety of data sources were used to create the geomorphologic map) by which the shape, extent and location of geomorphologic features on the topographic map have been improved and confirmed This research reviewed the main geomorphologic phenomena present in the study area and their distribution, as a basis for further assessment of land and land use planning in the region, and thus they are considered important tools to guide spatial planning correctly in those areas, of which the study area is one of them.